The Environmental Critique of Water Fluoridation - Carstairs, Catherine (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2015)
While people often associate the opposition to community water fluoridation with the extreme right, most people opposed to fluoridation were concerned about the impact that it might have on health and the environment. In the 1960s and 1970s, anti-fluoridationists frequently mentioned the possibility that fluoride would accumulate in our bodies and in our environment, leading to long-term health problems. They were assisted by a new generation of scientists, interested in toxicology and environmental health, who began publishing articles critical of water fluoridation. By the 1970s, the environmental critique of water fluoridation was having a significant impact. For example, in the late 1970s, the legislation mandating compulsory water fluoridation in Quebec was suspended, largely because of environmental concerns. The debate over water fluoridation is just one example of how Canadians became more concerned about the relationship between the environment and human health in the second half of the twentieth century.